Islamic economics education in Indonesia: Quranic view and epistemological problems analysis: Pendidikan ekonomi Islam di Indonesia: Pandangan al-Quran dan analisis masalah epistemologi - Azwar, Azwar; Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi (al-Irsyad: Journal of Islamic and Contemporary Issues, 2022)
Responding to the great potential of Shariah-based economics, various higher education institutions in Indonesia are trying to make breakthroughs by establishing a study programme in Islamic economics. The issue stems from the fact that Islamic Economics is offered as a course at several Indonesian higher education institutions. Because economics and shariah have distinct philosophical scopes, it will indirectly result in epistemological issues in the philosophy of science. These epistemological issues need to be answered and resolved to ensure that the outcomes of these educational programmes do not conflict with the goals for which they were established. This study aims to provide solutions to these epistemological problems, particularly in the institutional environment or higher education institutions, and to analyse the Quranic view as well as the position and application of Islamic economics between the influence of economics and Fiqh al-Mu‘āmalah. The methods of content analysis and library research were utilised in this qualitative-descriptive study. The study’s results indicated that Islamic economics is not just a system or norm, as people have previously suspected, but also a scientific discipline discovered through scientific methodology. The position of Islamic economics between the influence of economics and Fiqh al-Mu‘āmalah challenging to combine them. The fundamental difference between them, especially in the epistemological aspect, requires thinking to synergize and integrate into the discipline of Islamic economics.